2007
DOI: 10.1074/jbc.m700084200
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Inhibitors of a Glycoside Hydrolase Attenuate Inducible AmpC-mediated β-Lactam Resistance

Abstract: The increasing spread of plasmid-borne ampC-ampR operons is of considerable medical importance, since the AmpC ␤-lactamases they encode confer high level resistance to many third generation cephalosporins. Induction of AmpC ␤-lactamase from endogenous or plasmid-borne ampC-ampR operons is mediated by a catabolic inducer molecule, 1,6-anhydro-Nacetylmuramic acid (MurNAc) tripeptide, an intermediate of the cell wall recycling pathway derived from the peptidoglycan. Here we describe a strategy for attenuating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
145
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 104 publications
(151 citation statements)
references
References 73 publications
6
145
0
Order By: Relevance
“…16,28 Moreover, we have demonstrated that AmpC mediated b-lactam resistance can be attenuated by inhibiting NagZ with these selective inhibitors. Attenuation has been achieved in a model system of E. coli harboring a plasmid encoding an ampC-ampR operon, 16 and more recently in the opportunistic pathogen P. aeruginosa. 29 The most selective inhibitor found to date is $100-fold selective for NagZ over the human b-hexosaminidase isoenzymes and O-GlcNAcase.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…16,28 Moreover, we have demonstrated that AmpC mediated b-lactam resistance can be attenuated by inhibiting NagZ with these selective inhibitors. Attenuation has been achieved in a model system of E. coli harboring a plasmid encoding an ampC-ampR operon, 16 and more recently in the opportunistic pathogen P. aeruginosa. 29 The most selective inhibitor found to date is $100-fold selective for NagZ over the human b-hexosaminidase isoenzymes and O-GlcNAcase.…”
mentioning
confidence: 99%
“…Although GH3 enzymes, including NagZ, are functionally related to the GH20 human b-hexosaminidase isoenzymes and GH84 O-GlcNAcase, recent kinetic [17][18][19] and structural studies 16,[20][21][22] have revealed that GH3 enzymes use a catalytic mechanism that differs from that used by GH20 and GH84 enzymes. This distinction should therefore offer a tractable route to generating selective inhibitors of NagZ, and clear comparisons of these enzymes at a structural level would greatly accelerate these efforts.…”
mentioning
confidence: 99%
See 3 more Smart Citations